LINK BUDGET ANALYSIS WITH COMPARISSON OF PROPAGATION MODELING IN CELLULAR COMMUNICATION URBAN AREA - Simarmata, Monica Pasu Aprilia; Soim, Sopian; Fadhli, Mohammad (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal); Vol 5 No 2: JETT Desember 2018, 2019)
High increasingly the need for wireless communication is lncreasing the need for cellular communication system, especially in urban area. The propagation media of cellular communication is air, which is it affecting quality of communication. The important think in link budget calculation is to able to build good communication system. This research was conducted with the calculation and measurment of RSL, the result will be analyzed and can be determined the appropite propagation model to be implemented in urban area of Palembang. This research uses PCS Extension to Hata model and SUI model in pathloss calculation and uses drive test method with G-Net Track in acquisition of measurement data. The distance range specified in 500 – 1500 m and located on 5 different sites. Based on this research, the propagation model that appropriating in urban area that has been evaluated is SUI model.